Efektivitas Penerapan Quantum Teaching Terhadap Hasil Belajar Siswa Pada Pembelajaran PAI di SMPN 2 Ampek Angkek - Hardi, Hafis; Monia, Fenny Ayu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research was motivated by the discovery that several students during the lesson were not serious about learning, this was proven by the number of students who slept while studying, liked to go in and out of class, felt bored while studying and went to the canteen while the lesson was taking place. This is due to learning that only focuses on the teacher center so that learning is watched which results in low student learning outcomes, especially for class VIII students. So, to overcome this problem, this research aims to determine the effectiveness of the quantum teaching model The research used in this research is quantitative experimental research. The population in this study were all class VIII students at SMPN 2 Ampek Angkek, where class VII.1 was the control class and class VII.II was the experimental class. The data in this study was collected through tests and analyzed using the independent sample t test. Based on the results of the research that has been carried out, it was found that the quantum technology model applied was more effective on student PAI learning outcomes than using the conventional model as proven by the results of the independent sample t test, namely at a sig value of 0.000 < 0.05 and at a calculated t value of > t table is 4.378 > 1.999.